Four-dimensional Flow MRI as a Marker for Risk Stratification of Gastroesophageal Varices in Patients with Liver Cirrhosis - Motosugi, Utaroh (Radiology, 2019)
PURPOSE: To assess the feasibility of four-dimensional (4D) flow MRI as a noninvasive imaging marker for stratifying the risk of variceal bleeding in patients with liver cirrhosis. MATERIALS AND METHODS: This study recruited participants scheduled for both liver MRI and gastroesophageal endoscopy. Risk of variceal bleeding was assessed at endoscopy by using a three-point scale: no varices, low risk, and high risk requiring treatment. Four-dimensional flow MRI was used to create angiograms for evaluating visibility of varices and to measure flow volumes in main portal vein (PV), superior mesenteric vein, splenic vein (SV), and azygos vein. Fractional flow changes in PV and SV were calculated to quantify shunting (outflow) from PV and SV into varices. Logistic analysis was used to identify the independent indicator of high-risk varices. RESULTS: There were 23 participants (mean age, 52.3 years; age range, 25–75 years), including 14 men (mean age, 51.7 years; age range, 25–75 years) and nine women (mean age, 53.2 years; age range, 31–72 years) with no varices (n = 8), low-risk varices (n = 8), and high-risk varices (n = 7) determined at endoscopy. Four-dimensional flow MRI–based angiography helped radiologists to view varices in four of 15 participants with varices. Independent indicators of high-risk varices were flow volume in the azygos vein greater than 0.1 L/min (P = .034; 100% sensitivity [seven of seven] and 62% specificity [10 of 16]) and fractional flow change in PV of less than 0 (P < .001; 100% sensitivity [seven of seven] and 94% specificity [15 of 16]). CONCLUSION: Azygos flow greater than 0.1 L/min and portal venous flow less than the sum of splenic and superior mesenteric vein flow are useful markers to stratify the risk of gastroesophageal varices bleeding in patients with liver cirrhosis. © RSNA, 2018 Online supplemental material is available for this article.